2019
DOI: 10.1111/febs.14938
|View full text |Cite
|
Sign up to set email alerts
|

A guide to visualizing the spatial epigenome with super‐resolution microscopy

Abstract: Genomic DNA in eukaryotic cells is tightly compacted with histone proteins into nucleosomes, which are further packaged into the higher‐order chromatin structure. The physical structuring of chromatin is highly dynamic and regulated by a large number of epigenetic modifications in response to various environmental exposures, both in normal development and pathological processes such as aging and cancer. Higher‐order chromatin structure has been indirectly inferred by conventional bulk biochemical assays on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 140 publications
(210 reference statements)
0
15
0
Order By: Relevance
“…Simply put, Hi-C does not measure absolute contact frequency, and 3D reconstructions of higher order chromatin organization from Hi-C data have sometimes been used to argue for relatively open and accessible lariat-like chromatin loop structures [69, 7376]. In contrast, recent studies using advanced microscopic strategies have suggested nucleosome clusters (NCs) as basic entities of chromatin organization beyond the nucleosome level [7779]. Chromatin loops built from NCs imply more compacted and less accessible CDs with profound consequences for their accessibility for macromolecules (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply put, Hi-C does not measure absolute contact frequency, and 3D reconstructions of higher order chromatin organization from Hi-C data have sometimes been used to argue for relatively open and accessible lariat-like chromatin loop structures [69, 7376]. In contrast, recent studies using advanced microscopic strategies have suggested nucleosome clusters (NCs) as basic entities of chromatin organization beyond the nucleosome level [7779]. Chromatin loops built from NCs imply more compacted and less accessible CDs with profound consequences for their accessibility for macromolecules (see below).…”
Section: Discussionmentioning
confidence: 99%
“…In order to test this hypothesis, it is necessary to explore the space-time compaction and accessibility of CDs. Super-resolved fluorescence microscopy, including single molecule localization microscopy (SMLM) and stochastic optical reconstruction microscopy (STORM), may become the methods of choice to measure absolute differences of DNA/chromatin compaction with spatial resolution at the nanometer scale [79, 84, 85], whereas chromatin accessibility can be probed indirectly with methods that allow to measure molecular diffusion rates [8689].…”
Section: Discussionmentioning
confidence: 99%
“…Integrative biophysical and biochemical research strategies are imperative for a better understanding of the dynamic nuclear architecture and the molecular mechanisms involved in the interplay between nuclear architecture and function, for review, see ref. []. Such strategies will be discussed in a subsequent review with a focus on high‐resolution studies of chromatin compaction amd accessibility (Cremer et al., in preparation).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…The past decade not only witnessed the emerging application of super-resolution microscopy in centrosome research but also in the study of many other subcellular organelles and structures, including chromatin, which is mostly resolved by SMLM (Bintu et al 2018;Birk 2019;Sieben et al 2018b;Wang et al 2016;Xu and Liu 2019), the centromere and kinetochore (Joglekar et al 2009;Wan et al 2009;Wynne and Funabiki 2016), the contractile ring (Laplante et al 2016;McDonald et al 2017), the nuclear pore complex (Hurt and Beck 2015;Loschberger et al 2012;Szymborska et al 2013), and the mitochondria (Brown et al 2010;Jakobs and Wurm 2014;Jans et al 2013).…”
Section: Applications Beyond Centrosomementioning
confidence: 99%